2016
DOI: 10.1111/pbi.12561
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of folate and its precursors in Mexican common bean (Phaseolus vulgaris L.)

Abstract: SummaryFolate (vitamin B9) deficiency causes several health problems globally. However, folate biofortification of major staple crops is one alternative that can be used to improve vitamin intakes in populations at risk. We increased the folate levels in common bean by engineering the pteridine branch required for their biosynthesis. GTP cyclohydrolase I from Arabidopsis (AtGchI) was stably introduced into three common bean Pinto cultivars by particle bombardment. Seed‐specific overexpression of AtGCHI caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Over-expression (OE) of the GTP cyclohydrolase I (GCHI) ( Figure 4B), the first committed step in the pteridine pathway [167], in Arabidopsis resulted in a >1000-fold increase in pterins and only a 2-to 4-fold increase in folates (Table 3) [166]. Similar results were also observed following Seed-specific over-expression of GCHI in common Mexican bean [168]. These results were supported by similar work carried out by Diaz de la Gaza [164] who demonstrated that the OE of GCHI in tomato fruit resulted in an up to 140-fold increase in pterins and increased fruit folate content by an average of 2-fold [164].…”
Section: Genetic Manipulation Of Folate (Vitamin B 9 ) Accumulationsupporting
confidence: 69%
See 1 more Smart Citation
“…Over-expression (OE) of the GTP cyclohydrolase I (GCHI) ( Figure 4B), the first committed step in the pteridine pathway [167], in Arabidopsis resulted in a >1000-fold increase in pterins and only a 2-to 4-fold increase in folates (Table 3) [166]. Similar results were also observed following Seed-specific over-expression of GCHI in common Mexican bean [168]. These results were supported by similar work carried out by Diaz de la Gaza [164] who demonstrated that the OE of GCHI in tomato fruit resulted in an up to 140-fold increase in pterins and increased fruit folate content by an average of 2-fold [164].…”
Section: Genetic Manipulation Of Folate (Vitamin B 9 ) Accumulationsupporting
confidence: 69%
“…In tomato fruit, OE of GCHI was also shown to result in the depletion of the chloroplast synthesized PABA, which suggested that PABA represents a further limiting step in folate biosynthesis in transgenic tomato fruit (Table 3). However, this depletion in PABA is in contrast with an increase observed following the OE of GCHI in Mexican bean [168]. These authors demonstrated that feeding fruit PABA though the fruit stalk could increase folate by up to 10-fold [164].…”
Section: Genetic Manipulation Of Folate (Vitamin B 9 ) Accumulationmentioning
confidence: 87%
“…Folate determination and quantification were performed as previously described [43,44] with minor modifications. 100 mg of freeze-dried potatoes were ground in liquid nitrogen and extracted in 10 mL of folate extraction buffer (50 mM HEPES, 50 mM CHES, 10 mM β-mercaptoethanol, 2% ascorbic acid, 4 mM CaCl 2 , pH 7.85) and boiled for 10 min for folate release.…”
Section: Folate Analysis By Hplcmentioning
confidence: 99%
“…Genetic engineering is a powerful tool to introduce genes from sources that are inaccessible through sexual hybridization [12][13][14]. Thus, substantial efforts have been made to develop reliable transformation methods for engineering common beans with various traits [13,[15][16][17][18][19][20][21]. To date, no genetically engineered (GE) common bean has been commercialized, despite of the regulatory approval for the transgenic "Embrapa 5.1" common bean for golden mosaic virus (BGMV) resistance in Brazil in 2011 [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Stable transformation of common bean at low frequencies (< 1%) has been achieved using particle bombardment-mediated transformation of meristematic tissues for different goals [11,27,28]. Agrobacterium tumefaciens-mediated transformation is desirable for common bean transformation because of its accessibility and tendency to produce low-or single-copy insertion(s) of the transgene [18].…”
Section: Introductionmentioning
confidence: 99%